Improving Service Quality of A Private Hospital to Provide Satisfaction Of BPJS Participants - Singgih, Rahadi Pratomo; Pratiwi, Ayu; Yusyanah, Yusyanah; Sari, Mira Permata; Poernomo, Baby (Civil Officium: Journal of Empirical Studies on Social Science, 2023)
Health services are the most basic public services that must be carried out by the government to achieve a prosperous society. It is on this basis that the Government needs to improve the quality of public health with social security, namely the National Health Insurance (JKN), through the Health Social Security Administration Agency (BPJS). The focus of this research is how on the quality of health services provided by a private hospital to BPJS participants. This is a qualitative research with a case study approach. This study aims to answer the questions about the quality of service at hospital X in Bogor City for BPJS participants and what efforts should be made to provide satisfaction to BPJS participants. Data collection was carried out by observation, documentation, and semi-structured interviews with ten BPJS participants and an expert in the field of public policy. The results of this study indicate that the service quality of hospital X in Bogor City that consists of tangible, reliability, responsiveness, assurance and empathy still needs to be improved to provide satisfaction to BPJS health participants.